Owalla Reservoir in South-western Nigeria: Assessment of Fish Distribution, Biological Diversity, and Water Quality Index - Iyiola, Adams Ovie; Izah, Sylvester; Morya, Sonia; Akinsorotan, Ademola; Ogwu, Matthew (Talenta Publisher, 2023)
The Water Quality Index (WQI) was used to evaluate the ecological health and status of Owalla Reservoir and the implications on fish species distribution and biological diversity of the reservoir. Water quality and fish species were collected from three sampling zones (A, B, and C) from September 2019 to August 2020 and biological diversity indices such as dominance, Shannon-Weiner, Evenness, Brillouin, Menhinick, Margalef, Equitability, and Fishers index were calculated. The mean values measured for the temperature (25.9 ± 0.48 oC), dissolved oxygen (4.14 ± 0.10 mg/L), pH (7.0 ± 0.01), and nitrate (0.68 ± 0.25 mg/L) of Owalla Reservoir were within the recommended range; while ammonia (0.13 ± 0.20 mg/L), nitrite (0.14 ± 0.21 mg/L) were high and above the recommended limits. The WQI was highest in zone A (155.97) with an overall index value of 152.73 for the reservoir. Zone A recorded the highest relative fish abundance (49.95%) and was more diversified than other sampling zones. In terms of fish biodiversity indices, zone A had the highest richness (9), number of individuals (136), Shannon (1.84), and Brillouin (1.62) index values. Zones B and C were highest in terms of Dominance (1.0), and Evenness (1.0). Zones A and C were highest in terms of Simpson (0.83); zone B was highest in terms of Menhinick (1.58), and Fisher_alpha index (3.98) while zone C was highest in terms of Margalef (2.0), and Equitability (0.99) indices. The elevated levels of WQI, ammonia, and nitrite pose a danger to fish species and watershed systems. It is important to maintain the quality of water within Owalla Reservoir by ensuring best human practices and averting inappropriate human wastes as well as sewage disposal and agricultural activities. These should be checked for the sustainability of fish species.